PENGARUH BUDAYA ORGANISASI DAN PELATIHAN TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI DALAM MENINGKATKAN PENDAPATAN RUMAH SAKIT PELABUHAN JAKARTA - Naharuddin,; Nasharuddin Mas,; Irfany Rupiwardani, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
The purpose of this study was to analyze the influence of organizational culture and training on employee performance with job satisfaction as a mediating variable in increasing the income of the Jakarta Port Hospital. The population in this study were all employees of the Jakarta Port Hospital totaling 839 employees. Because the population size can be identified, the Slovin formula can be used to determine the sample size of the population, which is 89 employees. The data analysis technique used in this study was Partial Least SquareStructural Equation Modeling (PLS-SEM) using smartPLS software version 4. The results showed that organizational culture significantly influenced employee performance. Training significantly influenced employee performance. Organizational culture significantly influenced job satisfaction. Training significantly influenced job satisfaction. Job satisfaction significantly influenced employee performance. Job satisfaction mediates the influence of organizational culture on employee performance. Job satisfaction mediates the influence of training on employee performance. Employee performance significantly influenced Hospital income.